Biology of the human choroid - Mullins, Robert F. (Henry Stewart Talks, 2016)
Ocular anatomy, Comparison of retinal and choroidal vasculature, Microanatomy of the choroid and choriocapillaris, Cell types of the human choroid, Choriocapillaris development: hemovasculogenesis